(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The approach based on the law of gravity for the study of international trade flows has been widely used in recent years. Gravity model based studies have achieved empirical success in explaining various “flows”, for example international trade. Due to simplicity, high explanatory ability and improved econometrics the model is convenient as an examination tool for the researchers. The objective of this research is to provide an overview of the EU enlargement process in the period between 2000 and 2010 by means of a gravity model, as well as to estimate and measure the trade growth as a consequence of the opening up of the trade in the EU. Analysing the trade prospects for the new EU member states is important in the context of European enlargement. My research question is the following: what was the effect of EU enlargement on trade within and outside the EU? I find that the EU enlargement has large and significant effects on both old and new members’ trading activities. Old and new members both increased their exports; new members decreased their imports from the rest of the world. The relevant source of novelty to research lies in the methodology of the econometric model. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.